Understanding of Developing and Setting Tasks in Geography Lessons by German and Dutch Student Teachers - Krause, Uwe; Budke, Alexandra; Maier, Veit (Education sciences, 2021)
Setting tasks plays a key role in geography lessons, as they enable students to engage with the subject content, guide lessons towards predefined learning outcomes, and are therefore important for assessment. At the same time, the use of tasks is complex as numerous aspects regarding the content and the students have to be taken into account. Based on theoretical and empirical literature, we identify seven quality criteria for tasks in geography education: motivating and engaging students; addressing the heterogeneity of students; structuring learning processes; comprehensible formulation; considering individual and social learning processes; making meaningful use of materials; and fostering the development of subject specific competences. These criteria were applied in observation of lessons, which were given during an exchange between student geography teachers from a Dutch and German university. Overall, it was found that student teachers recognize the defined quality criteria, but half of them focus on only one or two aspects. The difficulties student teachers face in task setting during their traineeship can partly be explained by their phase of apprenticeship and the context. The developed observation form was considered to be valuable for preparation and observation of and reflection on tasks in geography lessons, and the exchange enabled student teachers to gain an insight into their own teaching practice. (Orig.).